Influence of Histone Deacetylase Inhibitors and DNA-Methyltransferase Inhibitors on the NK Cell-Mediated Lysis of Pediatric B-Lineage Leukemia - Pfeiffer, Matthias M.; Burrow, Helen; Schleicher, Sabine; Handgretinger, Rupert; Lang, Peter (Frontiers in Oncology, 2013)
Epigenetic drugs like histone deacetylase inhibitors and DNA methyltransferase inhibitors have been shown to be effective against a variety of tumor entities. Among different molecular anticancer activities of epigenetic active substances, up-regulation of NK cell ligands was described to contribute to an enhanced NK cell-mediated killing of tumor cell lines. So far, no data is available on this effect in childhood acute lymphoblastic leukemia. We investigated the effect of two HDACi (vorinostat, VPA) and two DNMTi (azacytidine, decitabine) on the viability, expression of NK ligands and NK-susceptibility of the pre-B-cell-ALL cell line MHH-CALL-4. Whereas vorinostat, azacytidine and decitabine directly reduced viability of the cell line, VPA had no direct cytotoxic effect. NKG2D ligands were expressed only at very low levels and not affected by epigenetic treatment. Higher expression was found for the DNAM1 ligands with significant up regulation of CD112 after treatment with VPA (p=0.02). No significant increase in lysis mediated by resting NK cells could be observed, whereas incubation of target cells with decitabine resulted in a significant increase in lysis mediated by IL-2 activated NK cells (p=0.0051, p=0.06 for azacytidine). Vorinostat and VPA could increase the lysis by expanded NK cells which was statistically not significant due to high inter-individual variability. Furthermore, HDACi but not DNMTi reduced the NK mediated lysis of MHH-CALL-4 after incubation of effector cells. In conclusion, there is a synergistic effect between epigenetic drugs and NK cells against MHH-CALL-4 which is not as strong as in other tumor entities. In situations where NK mediated control of leukemia is assumed or wanted, a sophisticated combination of single epigenetic drugs and ex vivo expanded NK cells is needed to maximize the synergistic effect of both treatment strategies and DNMTIs may be preferred based on the direct inhibitory effect of HDACi on NK cell cytotoxicity.